Technical assessment of discarded tires gasification as alternative technology for electricity generation - Machin, Einara Blanco [UNESP]; Pedroso, Daniel Travieso [UNESP]; de Carvalho, João Andrade [UNESP] (My University, 2017)
Concern about contamination associated with the disposal of tires has led to the search for technologies to reuse discarded tires, which include the use of Tire Derived Fuel (TDF) as fuel in advanced thermal-conversion processes, this allows the energy use of these wastes at affordable costs and reduces the environmental impact on scrap tires disposal. A theoretical assessment of the technical viability of TDF gasification for electric and thermal power generation, from the producer gas combustion in an internal combustion engine and in a gas turbine, was performed. The combustion of producer gas derived from the gasification of TDF in an internal combustion engine driving a generator (ICE-G) appears as the more efficient route for electricity generation when compared with the efficiency obtained with the use of gas turbine (GT-G). A higher global efficiency, considering the electric and thermal generation efficiency can be expected with the use of TDF producer gas in GT-G, where is expected an overall efficiency of 77.49%. The assessment shows that is possible produces up to 7.67 MJ and 10.62 MJ of electric and thermal energy per kilogram of TDF gasified using an ICE-G and up to 6.06 MJ and 13.03 MJ of electric and thermal energy respectively per kilogram of gasified TDF using a GT-G.
Keywords: Bubbling Fluidized Bed; Cogeneration; Gasification; Tire Derived Fuel; Used tires